Miniature Spears in the Viking Age: Small Symbols of Óðinn? - Gardeła, Leszek (Religionsvidenskabeligt Tidsskrift, 2022)
ABSTRACT: The spear is doubtlessly one of the most iconic weapons of the Viking Age. In addition to its numerous applications in armed conflict, where it was used by foot- and horseback warriors, the spear served as a potent emblem of power and social prominence. Furthermore, archaeological discoveries of spears in ritual contexts demonstrate unequivocally that these weapons played important roles in pre-Christian religious practice, in some instances perhaps echoing myths about Óðinn. This paper examines a group of rare Viking Age miniatures shaped like spears and spearheads. Made of a variety of materials, including iron, silver, copper alloys and wood, these intriguing artefacts were probably carried on the body singly or as part of elaborate sets of religious paraphernalia. By investigating the contexts of their discovery, as well as their materiality and different practical applications, new ideas will be offered about the miniature spears’ social and symbolic significance. RESUME: Spyddet er utvivlsomt et af de mest ikoniske våben fra vikingetiden. I tillæg til dets mange funktioner i væbnede konflikter, hvor det blev brugt af krigere til fods og til hest, var spyddet også et stærkt symbol på magt og social status. Ydermere viser arkæologiske fund af spyd i rituelle kontekster utvetydigt, at disse våben spillede en vigtig rolle i førkristen religiøs praksis, i nogle tilfælde måske forbundet med myter om Odin. Denne artikel undersøger en gruppe af sjældne miniaturer fra vikingetid, der er formet som spyd og spydspidser. Disse spændende genstande er fremstillet af forskellige materialer, såsom jern, sølv, kobberlegeringer og træ, og de blev sandsynligvis båret på kroppen som enkeltgenstande eller som del af mere omfattende sæt af religiøst udstyr. Ved at undersøge den kontekst, hvori de findes, samt materialer og diverse praktiske anvendelser byder artiklen på nye idéer om miniaturespyddenes sociale og symbolske betydning(er).